PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA PETUGAS LAPANGAN KELUARGA BERENCANA (PLKB) ) DALAM PENGELOLAAN PROGRAM KB DI KOTA PALU - Irmawati, Irmawati; Hasanuddin, Bakri; Adda, Harnida (Katalogis, 2018)
This study intends to determine and analyze: 1) simultaneous influence of competency and motivation on the performance of family planning field workers in managing the family planning programs in Palu; 2) the influence of competency on the performance of family planning field workers in managing the family planning programs in Palu; 3) the influence of motivation on the performance of family planning field workers in managing the family planning programs in Palu. Population and sample of study cover the family planning field workers who are civil servants and honorary employees of 52 people. Data analysis is multiple linear regressions analysis. The result indicates that competency and motivation simultaneously influence the performance of family planning field workers in managing the family planning programs in Palu of 43,4 %, while the remaining of 56,6 % influenced by other variables that are not studied.